Successful recovery from critical COVID-19 pneumonia with extracorporeal membrane oxygenation: A case report. (2020) - Ikuyama, Yuichi; Wada, Yosuke; Tateishi, Kazunari; Kitaguchi, Yoshiaki; Yasuo, Masanori; Ushiki, Atsuhito; Urushihata, Kazuhisa; Yamamoto, Hiroshi; Kamijo, Hiroshi; Mita, Atsuyoshi; Imamura, Hiroshi; Hanaoka, Masayuki
Abstract: A public health emergency of current international concern is the outbreak of a severe respiratory illness, that is, coronavirus disease (COVID-19). The disease initially started in Wuhan, China, and it rapidly spread to most regions of the world. Herein, we report a case of critical COVID-19 pneumonia treated with extracorporeal membrane oxygenation from symptom onset day 19 (SOD#19) to SOD#30. We describe the patient's clinical course, from mild symptoms at the time of illness onset to symptoms of severe pneumonia as the illness progressed. We provide important information regarding our clinical experience for further understanding of management discrepancies, as treatment with extracorporeal membrane oxygenation or pharmacotherapy (e.g., antivirals, immunomodulators, and glucocorticoids) is often dependent on the severity of symptoms. Highlights: A critical case of 76-year-old female with COVID-19 pneumonia. No significant clinical benefits of lopinavir-ritonavir and peramivir treatment. The pneumonia rapidly progressed to acute respiratory distress syndrome. Extracorporeal membrane oxygenation from illness day 21–31 lead to recovery.